2016
DOI: 10.7841/ksbbj.2016.31.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging Effects of Musa sapientum L. (Banana) Leaf Extract

Abstract: To examine the possibility of using Musa sapientum L. (Banana) leaf extract as a cosmetic raw material, banana leaves grown in Jeju Island were extracted with 70% ethanol. Polysaccharides present in banana leaf extract were discarded by precipitation with cold ethanol. Polysaccharidediscarded banana leaf extract promoted procollagen and COL1A1 gene expression, but inhibited matrix metalloproteinase (MMP)-1 and MMP-2 gene expression in human skin fibroblasts when examined by real-time reverse-transcription poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…MMPs degrade extracellular matrix (ECM) components, such as collagen, elastin, and gelatin. Of the known MMPs, MMP1 encodes interstitial collagenase, specifically degrading the collagen triple helix, while MMP2 encodes gelatinase A, degrading denatured collagen, gelatin, and elastin [ 29 ]. About 30% of the human body's proteins are collagen.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs degrade extracellular matrix (ECM) components, such as collagen, elastin, and gelatin. Of the known MMPs, MMP1 encodes interstitial collagenase, specifically degrading the collagen triple helix, while MMP2 encodes gelatinase A, degrading denatured collagen, gelatin, and elastin [ 29 ]. About 30% of the human body's proteins are collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Different parts of M. sapientum used for antioxidant activity tests, such as fruit peel, pulp, seed and flower, showed antioxidant potential of the plant, especially the fruit in different concentrations and different solvents used in the extraction [20,22,23,58,59,56,60].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Aesthetics is an area that is growing in the market, thus necessitating the search for natural cosmetics that have the ability to combat the main complaints. Fibroblasts are responsible for the production of collagen and elastin that contribute to the fight against aging in the aesthetic context, Yoo et al ( 2016) [60] concluded that the ethanolic extract of M. sapientum leaves has the ability to promote the expression of procollagen and COL1A1 genes, demonstrating the ability to be a raw material of a cosmetic with efficacy in wrinkles.…”
Section: Anti-wrinkle Activitymentioning
confidence: 99%